A method for preparing a simulated ancient textile mineralization sample
By aging and mineralizing modern silk samples, mineralized samples for simulated ancient textiles were prepared, which solved the problem that it was difficult to simulate mineralized silk cultural relics in the existing technology, and achieved the development of efficient simulation and cultural relics detection technology.
Patent Information
- Application Number
- CN202310345635.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-03
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2043-04-03
AI Technical Summary
The existing technology is difficult to effectively simulate mineralized silk cultural relics, resulting in limited development of cultural relics detection technology.
Mineralized samples of simulated ancient textiles were prepared by aging and mineralizing the modern silk samples in sequence. The aging stage uses enzyme treatment and humid heat conditions to simulate the biological aging process of silk, and the mineralization process is simulated by alkaline buffer and saturated metal ions.
It has achieved efficient simulation of mineralized silk cultural relics, avoided damage to cultural relics samples, promoted the development of mineralized cultural relics detection technology, and has the advantages of short time, high efficiency, low cost and simple operation.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silk cultural relic simulation, and more specifically relates to a method for preparing a simulated ancient textile mineralization sample. Background Art
[0002] When cultural relics workers want to obtain information behind silk cultural relics, they often face a problem - related tests will consume cultural relic samples. For example, when developing a new type of cultural relic detection technology, it is inevitable to destroy the cultural relic itself and consume a large number of cultural relics, especially relatively fragile mineralized silk cultural relics, which has led to the stagnation of cultural relic-related technologies.
[0003] Mineralization refers to the replacement of some organic components in silk with inorganic components. The number of mineralized silks excavated now is even rarer than that of aged silk. Mineralized fabrics can only be excavated near metal vessels used as burial objects, and the excavated mineralized fabrics are more fragile. Repeated sampling will seriously damage the mineralized cultural relics. These reasons have further hindered the development of mineralized cultural relics detection technology.
[0004] At present, scientific researchers have developed a large number of technologies for aging simulation of ancient textiles, but have not involved the field of mineralization simulation. Using artificial simulation of mineralized samples to develop new testing technologies can not only avoid the large-scale loss of cultural relics samples, but also promote the development of cultural relics testing technology. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a method for preparing a simulated ancient textile mineralized sample. By aging modern silk samples and then mineralizing them, a simulated ancient textile cultural relic mineralized sample is obtained, which can restore the mineralization process to the greatest extent and make it better used in the study of mineralized cultural relics.
[0006] To achieve the above object, the present invention provides a method for preparing a simulated ancient textile mineralization sample, comprising the following steps:
[0007] (1) soaking the silk fabric in an ethanol aqueous solution, taking it out, washing it, and drying it;
[0008] (2) Soaking in an alkaline solution, then taking out, cleaning and sterilizing;
[0009] (3) adding chymotrypsin and an enzyme catalyst into an acidic buffer to obtain a solution A; then soaking the silk fabric treated in step (2) in the solution A and storing it in a constant temperature sterile environment; then taking it out, inactivating the enzyme and then washing it;
[0010] (4) placing the silk fabric in a constant temperature and humidity environment for aging, spraying water once at regular intervals, and obtaining an aged silk fabric;
[0011] (5) The aged silk fabric is immersed in an alkaline buffer solution containing saturated metal biocidal ions for mineralization to obtain a mineralized sample.
[0012] The present invention uses modern silk samples to prepare simulated ancient textile cultural relics mineralization samples. Due to the presence of sericin on the surface of silk, the aging and degradation of the internal structure is well protected. According to the actual process of textile mineralization, the simulation process is divided into two stages: aging stage and mineralization stage. Silk must be aged before mineralization. Compared with cellulose fibers, silk reacts more slowly because it is more tightly packed and lacks disulfide bonds.
[0013] In the aging stage, the silk is washed and first degraded with alkali solution to slightly damage the surface sericin protective layer, and then treated with enzymes to destroy the polypeptide structure of the silk. The enzyme can simulate the biological aging state of silk when it is buried underground to the greatest extent. Mild enzyme promoters can accelerate the enzyme aging time without causing serious damage. At the same time, wet heat aging is used to restore this process to the greatest extent. The stable polypeptide structure of silk is not easy to mineralize directly. The initial condition of mineralization is the aging of the textile. Therefore, after the aging treatment, some polypeptide chains are opened, and the structure of the silk itself is no longer tight, which is easy for inorganic matter to replace organic matter in the mineralization stage.
[0014] In the mineralization stage, the type of mineralization of cultural relics is determined by the metal products near the cultural relics. Therefore, according to the different metal ions, it can be divided into copper, iron, silver, calcification, etc., so different solutions can be selected to simulate different types of mineralization. The first step of mineralization occurs - the dissolution of biocidal metal cations, and this process is simulated by directly configuring the buffer. Combined with the actual excavation report, mineralized textiles are often excavated from soil environments with special physical and chemical properties. Therefore, an alkaline buffer is used as a base, and ions that promote mineralization, such as copper ions, iron ions and calcium ions, are added. The second step of mineralization is the transmission of metal cations with water. This process is simulated by soaking silk fabrics in a supersaturated solution. In a saturated solution, the precipitation of ions and the solution are in a dynamic equilibrium process. The precipitated ions are deposited downward. When the ions are deposited on the fiber surface, the replacement of organic and inorganic matter occurs, and the maximum reduction mineralization process has been achieved. In this process, mineralization and aging occur simultaneously, but the mineralization of silk is much stronger than the aging of silk, so that the simulation effect of the mineralization sample can be maximized.
[0015] The simulated cultural relic mineralized sample prepared by the present invention can be used for a new testing method for studying mineralized cultural relics, and the preparation method has the advantages of short time, high efficiency, low cost, and simple operation.
[0016] Further preferably, in step (1), the silk fabric is a silk fabric; the volume fraction of ethanol in the ethanol aqueous solution is 40-80%, and the soaking time is 3-5 minutes; and the drying temperature is 20-35°C.
[0017] Further preferably, in step (2), the pH of the alkaline solution is 7.5-8.5, the temperature is 20-35°C, and the immersion time is 25-45 min; the sterilization is 100-140 kPa high-pressure steam sterilization, and the sterilization time is 15-30 min.
[0018] If the alkalinity is too strong, it will cause great damage to the silk and the simulation environment will not be realistic enough. If the alkalinity is too weak, it will not destroy the silk structure in a short time.
[0019] Further preferably, in step (3), the pH of the acidic buffer solution is 5-6.5.
[0020] The buffer solution is used because the enzyme treatment time is relatively long, and the weakly acidic environment is to ensure the activity of chymotrypsin and enzyme catalyst.
[0021] Further preferably, the amount of chymotrypsin added is 1 / 4000-1 / 6000 of the mass of the acidic buffer; the ratio of the amount of chymotrypsin added to the enzyme catalyst is 1:2-4; the enzyme catalyst is 8-((4-(2,4-dimethoxyphenyl)piperazine-1-yl)methyl)-5,7-dihydroxy-3-(4-hydroxyphenyl)-4H-benzopyran-4-one, that is, a papain promoter.
[0022] The use of chymotrypsin and protease promoter under acidic conditions is to destroy the structure of the silk peptide chain and further age it. Using too little chymotrypsin and protease promoter will take more time; too much will excessively destroy the silk peptide chain, resulting in poor simulation effect. If an alkaline buffer is used, the silk chain segments will undergo random hydrolysis, resulting in poor aging effect.
[0023] Further preferably, the temperature of the constant temperature sterile environment is 35-40°C, and the storage time is 5-7 days.
[0024] Too high a temperature will cause the enzyme to be inactivated, while too low a temperature will affect the aging effect.
[0025] More preferably, the temperature for inactivating the enzyme is 100-120° C., and after inactivating the enzyme, the mixture is washed with a sodium carboxymethyl cellulose aqueous solution having a mass fraction of 1-2%, and the number of washing times is 2-5 times.
[0026] Further preferably, in step (4), the aging temperature is 50-60° C., the relative humidity is 50-60%, and the aging time is 6-8 days.
[0027] Increasing the temperature, humidity and time will accelerate the aging of silk, otherwise the aging effect will not be achieved. During this stage, the artificial mineralization sample finally produced has the best simulation effect.
[0028] Preferably, the water spraying interval is 12-24h, and the amount is 2-4mL / 100cm 2 .
[0029] Further preferably, in step (5), the pH of the alkaline buffer solution is 7.5-8.5, and saturated metal biocidal ions are also added to the alkaline buffer solution, and the metal biocidal ions are calcium ions, iron ions, copper ions or silver ions; the immersion time is 20-40 days, and the temperature is 20-40°C.
[0030] If the alkalinity of the alkaline buffer is too strong, the protein will be over-denatured, and if the alkalinity is too weak, the aging effect will be too poor. The mineralization stage is often accompanied by the aging of silk. The alkaline environment is selected to better promote the mineralization effect and obtain a mineralized sample. If an acidic solution is used, the aging effect in this stage will be greater than the mineralization effect, and the simulated ancient textile aging sample will be obtained instead of a mineralized sample. Ca ions can cause calcification of textiles; Fe ions can cause ironization of textiles; Cu ions can cause copperization of textiles.
[0031] The reasons for mineralization are complex, since mineralization of silk depends mainly on the burial environment. In fact, mineralization depends mainly on the type of buried metals adjacent to the textile. Silk wrapped in copper objects is prone to copperization, textiles wrapped in iron objects are prone to ironization, textiles wrapped in silver objects are prone to silverization, and textiles wrapped in human bones are prone to calcification. Therefore, adding saturated Ca ions to an alkaline buffer can simulate calcification of textiles; adding saturated Fe ions can simulate ironization of textiles; adding saturated Cu ions can simulate copperization of textiles; adding saturated Ag ions can simulate silverization of textiles.
[0032] Compared with the prior art, the present invention has the following advantages: by subjecting modern silk samples to an aging stage and a mineralization stage in sequence, a simulated ancient textile cultural relic mineralized sample is obtained; after the aging treatment is completed, it is easier to replace organic matter with inorganic matter in the mineralization stage, different solutions can be selected to simulate different types of mineralization, and the mineralization process can be reduced to the greatest extent. This is a new testing method for studying mineralized cultural relics, and has the advantages of short time, high efficiency, low cost, and easy operation. DETAILED DESCRIPTION
[0033] The technical content and effects of the present invention are further described in detail below in conjunction with the embodiments, but the present invention is not limited thereto.
[0034] Example 1
[0035] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 50%) for 3 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 25°C;
[0036] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 8 at a temperature of 25° C. for 30 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 20 min;
[0037] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4 & KH2PO4 buffer solution at pH = 5.5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 5000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:3; placing the silk fabric treated in step (2) in solution A, and placing it in a sterile thermostat at a temperature of 40° C. for 7 days; taking it out, inactivating the enzyme at 120° C., and then washing it 3 times with a 1% sodium carboxymethyl cellulose aqueous solution;
[0038] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 50° C. and a relative humidity of 50% for aging for 7 days. During the aging period, the silk fabric was sprayed with distilled water once every 12 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 70%), soak for 3 minutes, soak 3 times; dry at 25 ° C to obtain aged silk fabric;
[0039] (5) CaCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH = 8 to saturate the calcium ions in the buffer solution, and the aged silk fabric was immersed in it at 25°C for 30 days to obtain a mineralized sample.
[0040] Example 2
[0041] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 75%) for 5 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 20°C;
[0042] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 7.5 at a temperature of 30° C. for 30 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 20 min;
[0043] (3) adding chymotrypsin and a catalyst (papain promoter) to a K2HPO4&KH2PO4 buffer solution at pH=6.5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 4000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:2; placing the silk fabric treated in step (2) in solution A, and placing it in a sterile thermostat at a temperature of 35°C for 5 days; taking it out, inactivating the enzyme at 120°C, and then washing it three times with a 2% sodium carboxymethyl cellulose aqueous solution;
[0044] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 50° C. and a relative humidity of 50% for 6 days. During the aging period, the silk fabric was sprayed with distilled water once every 24 hours at a spraying rate of 4 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 50%), soak for 5 minutes, soak 3 times; dry at 20 ° C to obtain aged silk fabric;
[0045] (5) CaCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH of 7.8 to saturate the buffer solution with calcium ions, and the aged silk fabric was immersed in the solution at 20°C for 40 days to obtain a mineralized sample.
[0046] Example 3
[0047] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 80%) for 3 minutes; after immersion, washing it twice with deionized water, laying it flat and drying it naturally at a temperature of 35°C;
[0048] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 8.5 at a temperature of 35° C. for 25 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 140 kPa high-pressure steam for 15 min;
[0049] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4 & KH2PO4 buffer solution at pH = 6.5 to prepare solution A, wherein the amount of chymotrypsin added is 1 / 6000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:4; then placing the silk fabric treated in step (2) in solution A, placing it in a sterile thermostat at a temperature of 35° C. for 7 days; taking it out, inactivating the enzyme at 120° C., and then washing it twice with a 2% sodium carboxymethyl cellulose aqueous solution;
[0050] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 60° C. and a relative humidity of 60% for 8 days. During the aging period, the silk fabric was sprayed with distilled water once every 12 hours at a spraying rate of 4 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 80%), soak for 3 minutes, soak 4 times; dry at 35 ° C to obtain aged silk fabric;
[0051] (5) CuCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH of 8.5 to saturate the copper ions in the buffer solution, and the aged silk fabric was immersed in it at 40°C for 20 days to obtain a mineralized sample.
[0052] Example 4
[0053] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 80%) for 3 minutes; after immersion, washing it twice with deionized water, laying it flat and drying it naturally at a temperature of 35°C;
[0054] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 7.8 at a temperature of 30° C. for 40 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 100 kPa high-pressure steam for 30 min;
[0055] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4 & KH2PO4 buffer solution at pH = 5.5 to prepare solution A, wherein the amount of chymotrypsin added is 1 / 5000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:3; then placing the silk fabric treated in step (2) in solution A, placing it in a sterile thermostat at a temperature of 40° C. for 5 days; taking it out, inactivating the enzyme at 110° C., and then washing it 4 times with a 1.5% sodium carboxymethyl cellulose aqueous solution;
[0056] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 60° C. and a relative humidity of 50% for aging for 7 days. During the aging period, the silk fabric was sprayed with distilled water once every 20 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 70%), soak for 4 minutes, soak 3 times; dry at 30 ° C to obtain aged silk fabric;
[0057] (5) Adding AgCl2 to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a pH value of 7.5 to saturate the buffer solution with silver ions, immersing the aged silk fabric at 30°C for 30 days to obtain a mineralized sample.
[0058] Example 5
[0059] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 75%) for 4 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 25°C;
[0060] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 8 at a temperature of 25° C. for 40 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 25 min;
[0061] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4&KH2PO4 buffer solution at pH=5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 4500 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:3; placing the silk fabric treated in step (2) in the solution A, and placing it in a sterile thermostat at a temperature of 40°C for 7 days; taking it out, inactivating the enzyme at 115°C, and then washing it 4 times with a 2% sodium carboxymethyl cellulose aqueous solution;
[0062] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 60° C. and a relative humidity of 50% for aging for 7 days. During the aging period, the silk fabric was sprayed with distilled water once every 18 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 75%), soak for 4 minutes, soak 4 times; dry at 25 ° C to obtain aged silk fabric;
[0063] (5) CuCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH of 7.5 to saturate the copper ions in the buffer solution, and the aged silk fabric was immersed in it at 35°C for 35 days to obtain a mineralized sample.
[0064] Example 6
[0065] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 50%) for 3 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 20°C;
[0066] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 7.5 at a temperature of 20° C. for 30 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 15 min;
[0067] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4&KH2PO4 buffer solution at pH=5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 4000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:2; placing the silk fabric treated in step (2) in solution A, and placing it in a sterile thermostat at a temperature of 35°C for 6 days; taking it out, inactivating the enzyme at 100°C, and then washing it twice with a 2% sodium carboxymethyl cellulose aqueous solution;
[0068] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 50° C. and a relative humidity of 50% for 6 days. During the aging period, the silk fabric was sprayed with distilled water once every 12 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 50%), soak for 3 minutes, soak 3 times; dry at 25 ° C to obtain aged silk fabric;
[0069] (5) CuCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH = 7.5 to saturate the copper ions in the buffer solution, and the aged silk fabric was immersed in it at 20°C for 40 days to obtain a mineralized sample.
[0070] Comparative Example 1 (the difference compared with Example 6 is that the silk was not fully aged during the aging stage)
[0071] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 50%) for 3 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 20°C;
[0072] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 7.5 at a temperature of 20° C. for 10 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 15 min;
[0073] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4&KH2PO4 buffer solution at pH=5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 4000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:2; placing the silk fabric treated in step (2) in the solution A, and placing it in a sterile thermostat at a temperature of 35°C for 3 days; taking it out, inactivating the enzyme at 100°C, and then washing it twice with a 2% sodium carboxymethyl cellulose aqueous solution;
[0074] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 50° C. and a relative humidity of 50% for aging for 3 days. During the aging period, the silk fabric was sprayed with distilled water once every 12 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 50%), soak for 3 minutes, soak 3 times; dry at 25 ° C to obtain aged silk fabric;
[0075] (5) CuCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH = 7.5 to saturate the copper ions in the buffer solution, and the aged silk fabric was immersed in it at 20°C for 40 days to obtain a mineralized sample.
[0076] Comparative Example 2 (the difference compared with Example 6 is that the silk is not fully mineralized during the mineralization stage)
[0077] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 50%) for 3 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 20°C;
[0078] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 7.5 at a temperature of 20° C. for 30 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 15 min;
[0079] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4&KH2PO4 buffer solution at pH=5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 4000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:2; placing the silk fabric treated in step (2) in solution A, and placing it in a sterile thermostat at a temperature of 35°C for 6 days; taking it out, inactivating the enzyme at 100°C, and then washing it twice with a 2% sodium carboxymethyl cellulose aqueous solution;
[0080] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 50° C. and a relative humidity of 50% for 6 days. During the aging period, the silk fabric was sprayed with distilled water once every 12 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 50%), soak for 3 minutes, soak 3 times; dry at 25 ° C to obtain aged silk fabric;
[0081] (5) CuCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH = 7 to saturate the copper ions in the buffer solution, and the aged silk fabric was immersed in it at 20°C for 10 days to obtain a mineralized sample.
[0082] Comparative Example 3 (the difference compared with Example 6 is that: due to the selection of an acidic solution in the mineralization stage, the mineralization effect is not as good as the aging effect, the silk is severely aged, and the simulation effect is poor)
[0083] (1) immersing the silk fabric in an ethanol aqueous solution (the volume fraction of ethanol is 50%) for 3 minutes; after immersion, washing it with deionized water for 3 times, laying it flat and drying it naturally at a temperature of 20°C;
[0084] (2) Soaking the dried silk fabric in a NaOH solution with a pH of 7.5 at a temperature of 20° C. for 30 min; washing with distilled water until the washing solution is neutral; washing twice with anhydrous ethanol and sterilizing with 120 kPa high-pressure steam for 15 min;
[0085] (3) adding chymotrypsin and an enzyme catalyst (papain promoter) to a K2HPO4&KH2PO4 buffer solution at pH=5 to prepare a solution A, wherein the amount of chymotrypsin added is 1 / 4000 of the mass of the buffer solution, and the ratio of the added chymotrypsin to the enzyme catalyst is 1:2; placing the silk fabric treated in step (2) in solution A, and placing it in a sterile thermostat at a temperature of 35°C for 6 days; taking it out, inactivating the enzyme at 100°C, and then washing it twice with a 2% sodium carboxymethyl cellulose aqueous solution;
[0086] (4) The silk fabric treated in step (3) was placed in a constant temperature and humidity aging box at a temperature of 50° C. and a relative humidity of 50% for 6 days. During the aging period, the silk fabric was sprayed with distilled water once every 12 hours at a spraying rate of 3 mL / 100 cm 2 ; After aging treatment, wash with ethanol aqueous solution (ethanol volume fraction is 50%), soak for 3 minutes, soak 3 times; dry at 25 ° C to obtain aged silk fabric;
[0087] (5) CuCl2 was added to the Na2HPO4 & NaH2PO4 alkaline buffer solution with a solution pH of 5.5 to saturate the copper ions in the buffer solution, and the aged silk fabric was immersed in it at 20°C for 40 days to obtain a mineralized sample.
[0088] Table 1
[0089]
[0090]
[0091] Comparative Example 1 shows that, because the silk was not fully aged during the aging stage, the silk after step (4) still had a relatively complete microstructure and a high degree of crystallinity. Such a structure prevented mineralization from occurring, so the silk did not undergo mineralization in step (5).
[0092] Comparative Example 2 shows that the mineralization is not obvious because the mineralization time is too short in the mineralization stage.
[0093] Comparative Example 3 shows that due to the use of an acidic solution in the mineralization stage, the aging degree of the silk fabric is much greater than the mineralization degree, that is, the corrosion degree does not match the mineralization degree, the simulation effect is poor, and the experiment fails.
[0094] The above embodiments of the present invention are merely examples for illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes and modifications can be made based on the above description. It is impossible to list all the embodiments here. Any obvious changes or modifications derived from the technical solution of the present invention are still within the scope of protection of the present invention.
Claims
1. A method for preparing a simulated ancient textile mineralization sample, characterized in that: The steps include: (1) Soak the silk fabric in ethanol water solution, take it out, wash it, and dry it; (2) Soak in an alkaline solution, then take out, clean and sterilize; (3) adding chymotrypsin and an enzyme catalyst into an acidic buffer to obtain solution A; Then, the silk fabric treated in step (2) is immersed in solution A and stored in a constant temperature sterile environment; then, it is taken out, inactivated, and then washed; (4) Place the samples in a constant temperature and humidity environment for aging. The aging temperature is 50-60°C, the relative humidity is 50-60%, and the aging time is 6-8 days. Spray water every once in a while. The spraying interval is 12-24 hours, and the dosage is 2-4mL / 100cm 2 , obtaining an aged silk fabric; (5) The aged silk fabric is mineralized by immersing it in an alkaline buffer solution containing saturated metal biocidal ions, wherein the metal biocidal ions are calcium ions, iron ions, copper ions or silver ions, the pH of the alkaline buffer solution is 7.5-8.5, the immersion time is 20-40 days, the temperature is 20-40°C, and a mineralized sample is obtained.
2. The method for preparing the simulated ancient textile mineralized sample according to claim 1, characterized in that: In step (1), the volume fraction of ethanol in the ethanol aqueous solution is 40-80%, the soaking time is 3-5 minutes, and the drying temperature is 20-35°C.
3. The method for preparing the simulated ancient textile mineralized sample according to claim 1, characterized in that: In step (2), the pH of the alkaline solution is 7.5-8.5, the temperature is 20-35°C, and the immersion time is 25-45 minutes; the sterilization is 100-140 kPa high-pressure steam sterilization, and the sterilization time is 15-30 minutes.
4. The method for preparing the simulated ancient textile mineralized sample according to claim 1, characterized in that: In step (3), the pH of the acidic buffer solution is 5-6.
5.
5. The method for preparing the simulated ancient textile mineralized sample according to claim 1, characterized in that: The amount of chymotrypsin added is 1 / 4000-1 / 6000 of the mass of the acidic buffer; the ratio of the amount of chymotrypsin added to the enzyme catalyst is 1:2-4; the enzyme catalyst is 8-((4-(2, 4-dimethoxyphenyl)piperazine-1-yl)methyl)-5, 7-dihydroxy-3-(4-hydroxyphenyl)-4H-benzopyran-4-one.
6. The method for preparing the simulated ancient textile mineralized sample according to claim 1, characterized in that: The temperature of the constant temperature sterile environment is 35-40° C., and the storage time is 5-7 days.
7. The method for preparing the simulated ancient textile mineralized sample according to claim 1, characterized in that: The temperature for inactivating the enzyme is 100-120° C. After the enzyme is inactivated, the method is washed with a sodium carboxymethyl cellulose aqueous solution having a mass fraction of 1-2%, and the number of washing times is 2-5 times.
Citation Information
Patent Citations
Production method of hydroxyapatite-functionalized silk fabric
CN104250926A
Method for mineralizing silk fiber
CN104928908A